Caffeic acid phenethyl ester protects against doxorubicin-induced cardiotoxicity and increases chemotherapeutic efficacy by regulating the unfolded protein response. (January 2022) - Zhang, Ying; Kong, Dezhi; Han, Han; Cao, YongJun; Zhu, HongXuan; Cui, Guozhen
Abstract: Doxorubicin (Dox) is an efficient drug used in breast cancer chemotherapy. However, the clinical application of Dox in cancer treatment is limited due to its cardiotoxicity. Caffeic acid phenethyl ester (CAPE) is a critical bioactive ingredient of honeybee propolis that possesses various beneficial pharmacological properties, such as antioxidant and anticancer activities. Here, we aimed to investigate the protective effect of CAPE on Dox-induced cardiotoxicity and its anti-breast cancer effects. CAPE significantly ameliorated Dox-induced toxicity in H9c2 cells and in a mouse model. Mechanistically, Dox caused endoplasmic reticulum (ER) dysfunction characterized by the activation of the unfolded protein response (UPR) and upregulation of Bax proteins, and CAPE attenuated the Dox-induced UPR in H9c2 cells. In contrast, CAPE significantly enhanced Dox-induced cytotoxicity in human breast cancer cells by upregulating the Dox-induced UPR; it also markedly suppressed tumor growth in 4T1 cancer-bearing BALB/c mice. In conclusion, CAPE could be used as a promising therapy for patients with cancer receiving Dox treatment. Graphical abstract: Image 1 Highlights: CAPE decreased doxorubicin-induced cardiotoxicity while improving the efficacy of anti-breast cancer drugs. CAPE has the potential to serve as a lead for attenuating cardiotoxicity and enhancing the anti-breast cancer activity. UPR is a promising strategy to attenuate cardiotoxicity and enhance the anti-breast cancer effects of doxorubicin.